Efficacy of a topical anaesthetic on pain during scaling and root planing: a double blind split mouth pilot study in patients with periodontitis - P. Shaju Jacob; SoniaNath (Universiti Kebangsaan Malaysia, 2013)
Scaling and root planing is one of the most commonly performed procedures in a dental clinic. Most patients will consider the procedure to be causing discomfort or even pain. Intrasulcular topical application of anaesthesia will be preferred over injectable anaesthetic by patients for reduction of pain during scaling and root planing. A double blind split mouth pilot study was designed to find if pain was associated with scaling and root planing and to assess if application of topical anaesthesia reduced the pain. Twenty one patients were enrolled to compare the effect of intrasulcularly applied 20% benzocaine with a placebo in reducing pain during scaling and root planing. Heft Parker Visual analog scale was used to record the level of pain experienced by participants during instrumentation. Independent samples and paired samples t test were used for statistical analysis. There was significant pain associated with scaling and root planing with placebo over baseline (p<0.01). There was significant reduction in pain in benzocaine applied side when compared with placebo (p<0.001). Pain level approached baseline in benzocaine applied side. In this study, pain was effectively and significantly reduced with intrasulcular application of 20% benzocaine in periodontitis patients.